1988
DOI: 10.1111/j.1523-1739.1988.tb00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Analysis in Nature Reserve Design: A New Zealand Example

Abstract: Absiract: Direct and indirect gradient analysis methods were tested to assist in nature reserve design in New Zealand Graphic descl-iptions were made of community-environment relationships. Environmental factors considered included altitude solar radiation, geologic substrate soil drainage, and landform. Classification identified 21 lowland forest community types in the northwestern South Island study area These community types and their composite species appear to be arranged along soil fertility, landfomz, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Other ordination studies of vegetation-environment relationships in New Zealand have also recognised the importance of differences in soil properties and altitude as the major factors influencing forest composition (Leathwick 1987;Stewart & Harrison 1987;DeVelice et al 1988;Leathwick et al 1988;Reif& Allen 1988;Duncan et al 1990;Norton & Leathwick 1990;Stewart et al 1993). However, in contrast to our results from Waipoua, in all studies (except two over small altitudinal ranges), altitude was the most important variable influencing species composition.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other ordination studies of vegetation-environment relationships in New Zealand have also recognised the importance of differences in soil properties and altitude as the major factors influencing forest composition (Leathwick 1987;Stewart & Harrison 1987;DeVelice et al 1988;Leathwick et al 1988;Reif& Allen 1988;Duncan et al 1990;Norton & Leathwick 1990;Stewart et al 1993). However, in contrast to our results from Waipoua, in all studies (except two over small altitudinal ranges), altitude was the most important variable influencing species composition.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…However, in contrast to our results from Waipoua, in all studies (except two over small altitudinal ranges), altitude was the most important variable influencing species composition. The second axis of the ordination was usually related to differences in soil properties, which were either tied to differences in soil development on different topographic units or landforms, as for DCA1 at Waipoua, or reflected soil rejuvenation occurring in dynamic landscapes through episodes of mass movement or windthrow (DeVelice et al 1988;Reif& Allen 1988;Stewart et al 1993).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…A further environmental factor that may affect species distributions in the Maungataniwha Range is variation in soil fertility./ks has been suggested by DeVelice et al (1988), soil fertility on a given parent material may vary with landtorm and soil disturbance. For example, flat terraces may be more highly leached of soil nutrients than slope,'; where recent mass soil movement has exposed relatively unweathered and nutrient-rich substrates.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study by DeVelice et al (1988) suggested the benefits of applying gradient analysis methods towards evaluating the representativeness of nature reserves in the Paparoa Range, New Zealand. The Paparoa study demonstrated the suitability of gradient analysis in an area charac terised by sharply defined vegetation/environmental patterns.…”
Section: Received 28 September 1987; Accepted 3 August 1988mentioning
confidence: 99%
“…Ecosystem representation, in combination with criteria to satisfy the other goals, such as distributions of threatened species, is a key component of prioritising sites for conservation (Austin and Margules 1986;DeVelice et al 1988;Scott et al 1993). Such representation can also provide the context for assessing the biodiversity impacts of a land-use change that will irrevocably alter natural ecosystems (Noss 1990;Crist et al 2000;Monavari and Momen Bellah Fard 2010), a problem to which it is less commonly applied in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%